2018
DOI: 10.1002/adma.201801430
|View full text |Cite
|
Sign up to set email alerts
|

Hollow‐Structured Metal Oxides as Oxygen‐Related Catalysts

Abstract: high overpotential and sluggish kinetics. Generally, Pt, IrO 2 , and RuO 2 noble metal catalysts have improved kinetics. But, the high cost and unsatisfactory long-term durability of noble-metal-based catalysts are the main limitations for large-scale commercial applications. Supplying flexible electronic structures, transition metal oxides are the optimal oxygen-related catalysts in which the adsorbents binding to metal cations (M) are neither too strong nor too weak. [9] With overall understanding of crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 76 publications
0
55
0
Order By: Relevance
“…Hollow nanostructures have exhibited desirable advantages as OER catalysts owing to their architectural features, such as large surface area, low density, multiple interfaces, and reduced diffusion lengths for mass transport. [ 25–27 ] Compared with single‐shelled hollow structures, hollow catalysts with the multi‐shelled feature exhibit apparent superiorities for electrocatalysis. [ 28–30 ] To be more specific, multi‐shells provide larger surface area and better utilization of the inner space.…”
Section: Figurementioning
confidence: 99%
“…Hollow nanostructures have exhibited desirable advantages as OER catalysts owing to their architectural features, such as large surface area, low density, multiple interfaces, and reduced diffusion lengths for mass transport. [ 25–27 ] Compared with single‐shelled hollow structures, hollow catalysts with the multi‐shelled feature exhibit apparent superiorities for electrocatalysis. [ 28–30 ] To be more specific, multi‐shells provide larger surface area and better utilization of the inner space.…”
Section: Figurementioning
confidence: 99%
“…In particular, transition metal phosphides, especially bimetallic transition metal phosphides have attracted significant attentions as bi-functional electrocatalysts for water-splitting owing to their remarkably enhanced catalytic activities [32,33]. To maximize the electrochemical performance of the catalysts, endowing the electrocatalysts with hollow nanostructures is regarded as an effective approach, which can significantly increase their specific surface areas and expose more reactive sites [34][35][36][37]. Moreover, the ion diffusion length and transport resistance for water splitting can be effectively reduced by their large void spaces, which has been fully demonstrated by previous studies [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has been reported that the surface atomic configuration of Co 3 O 4 was strongly influenced by its morphology [12]. Specially, metal oxides with hollow structures were demonstrated to possess more defect sites on their surfaces than the solid counterparts [13][14][15][16][17][18]. Therefore, we could reasonably speculate that fabrication of Co 3 O 4 with hollow structure may maximize the oxygen vacancies on its surface to achieve high catalytic efficiency in CO oxidation.…”
Section: Introductionmentioning
confidence: 88%